FINTECH SYARIAH DALAM PERSPEKTIF HUKUM ISLAM - Evan Hamzah Muchtar; Ahmad Zubairin (Jurnal Asy-Syukriyyah, 2022)
This study aims to determine Islamic fintech in the perspective of Islamic law with a qualitative descriptive method. The type of research used in this study is a literature study obtained from various sources. The results obtained indicate that Sharia fintech is a discussion of contemporary fiqh that has not been decided in the Qur'an and the Hadith of the Prophet SAW, thus using ijma (ulama consensus) as a source of law. The Indonesian Ulema Council issued the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) No. 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. The fatwa is in accordance with Islamic law and has clear legal protection and is contained in the legislation.